2007
DOI: 10.5424/sjar/2007053-247
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency analysis and decomposition of productivity growth of Spanish olive farms

Abstract: Spain occupies the first position in worldwide rankings of olive oil production and trade. This analysis assesses the relative technical efficiency with which this sector is operating. The concept of technical efficiency is critical to measuring the performance of a firm, determining the degree of innovative technology adoption and the overall production efficiency. Specifically, the main objective of this study is to assess the relative technical efficiency and to decompose the productivity growth of Spanish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 16 publications
3
28
1
Order By: Relevance
“…This simple statistical test further reinforced the assumption that there was a technical inefficiency of cocoa farming in the Central Sulawesi. This estimate was in accordance with previous work (Lambarraa et al, 2007).…”
Section: Estimated Results Of Production Function Of Cocoa Farmingsupporting
confidence: 82%
“…This simple statistical test further reinforced the assumption that there was a technical inefficiency of cocoa farming in the Central Sulawesi. This estimate was in accordance with previous work (Lambarraa et al, 2007).…”
Section: Estimated Results Of Production Function Of Cocoa Farmingsupporting
confidence: 82%
“…Several studies aim to explain the evolution and restructuring of farming structures, farm diversity and farm performance (e.g. Lambarra et al, 2007;Latruffe et al, 2012;Bojnec & Latruffe, 2013). Most of these studies, however, are restricted to a single country case, and when papers focusing on Gibrat's Law are considered, to non-transition economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Tzouvelekas et al, 1999), whereas it showed a decreasing trend in the case of the island of Crete, from 87.5% to 63.7% during the same period (Tzouvelekas, Giannakas, Midmore, & Mattas, 1997). Similarly, the estimated level of technical efficiency for Spanish olive farms was 75.5% on average during the period 1999-2002 (Lambarraa et al, 2007). For Tunisian olive farms, the estimated technical efficiency for the Mahdia region was 83.5% on the basis of data collected from 1999 to 2002 (Lachaal et al, 2004), whereas it was 82% for farmers in the Sfax region, over the period from 1994 to 1997 (Lachaal et al, 2005).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Lambarraa, Serra and Gil (2007) assessed relative technical efficiency by decomposing the productivity growth of Spanish olive-growing farms, and found that farm location, age of manager, and composition of the workforce affect efficiency levels. By looking at the heterogeneity of olive farms in Andalusia (Spain), such as the age of olive trees, irrigation, intensity of farming and land slope, Amores and Contreras (2009) examined farm efficiency using data envelopment analysis (DEA).…”
Section: Introductionmentioning
confidence: 99%